Pragmatic Variation: Compliment Responses of Malaysian Chinese Undergraduates in Two Academic Majors - Qi Ying Wu (PAROLE: Journal of Linguistics and Education, 2019)
AbstractThis study investigates compliment responses (CRs) produced by Malaysian Chinese undergraduates in Arts & Social Science and Science & Technology Studies. The purpose of this study is to determine the extent to which academic major influences compliment responses of participants from two major groups. The data of this study was collected from 30 Malaysian Chinese undergraduate students (15 in each major group) in one public university in Malaysia. The data was collected by role-play scenarios consisting of 4 situations (appearance, character, ability and possession) which were then accompanied by a questionnaire. The findings of the study show that there were no marked differences between the two academic major groups in the choices of their CRs strategies. Malaysian Chinese undergraduates’ CRs are greatly influenced by their English proficiency, politeness and Chinese culture. They tend to use Acceptance strategy at macro level. At micro level, both academic groups preferred Appreciation strategy which is under the macro strategy of Acceptance. On the contrary, Rejection was the least preferred CRs strategy.